Political interference on the airwaves: the BBC broadcasts to Portugal during the Second World War - Ribeiro, Nelson (2013)
The article analyses the impact of foreign broadcasts in Portugal during the Second World War as well as the communication strategies adopted by both German and British transmissions in the Portuguese language. After demonstrating that the broadcasts from the Axis powers were mainly composed of blatant propaganda, particular attention is given to the BBC. The British station, which was the most effective in reaching the Portuguese public, promoted itself as a credible source that offered reliable and unbiased news despite the fact that, as the article demonstrates, it trimmed its output to meet considerations imposed by the Foreign Office.